2016
DOI: 10.1002/chem.201602893
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Gold‐Catalysed Arylation of Heteroarenes: Complementarity to Palladium Catalysis

Abstract: Tailoring of the pre-catalyst, the oxidant and the arylsilane enables the first room-temperature, gold-catalysed, innate C-H arylation of heteroarenes. Regioselectivity is consistently high and, in some cases, distinct from that reported with palladium catalysis. Tolerance to halides and boronic esters, in both the heteroarene and silane partners, provides orthogonality to Suzuki-Miyaura coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 36 publications
(58 reference statements)
1
49
0
Order By: Relevance
“…In subsequent developments, Itami and Sagewa demonstrated that pyridylidene Au-complexation facilitates arylation of isoxazoles, indoles and benzothiophenes, 6 Jeon applied Aucatalyzed arylation to functionalize ortho-silyl aryl triflates generated via Rh/Ir-catalyzed traceless ortho-CH silation, 7 and we reported that silane and oxidant modification allows arylation of a range of heterocycles. 8 Major advances have also been made towards understanding the unique reactivity and selectivity of catalytic reactions proceeding via Au(I) and Au(III) intermediates. 6,9 Nonetheless, in comparison to many transition metal catalyzed processes, overall mechanistic understanding of homogeneous gold catalysis remains less well developed.…”
mentioning
confidence: 99%
“…In subsequent developments, Itami and Sagewa demonstrated that pyridylidene Au-complexation facilitates arylation of isoxazoles, indoles and benzothiophenes, 6 Jeon applied Aucatalyzed arylation to functionalize ortho-silyl aryl triflates generated via Rh/Ir-catalyzed traceless ortho-CH silation, 7 and we reported that silane and oxidant modification allows arylation of a range of heterocycles. 8 Major advances have also been made towards understanding the unique reactivity and selectivity of catalytic reactions proceeding via Au(I) and Au(III) intermediates. 6,9 Nonetheless, in comparison to many transition metal catalyzed processes, overall mechanistic understanding of homogeneous gold catalysis remains less well developed.…”
mentioning
confidence: 99%
“…As noted above neither 10 nor 18b undergo cyclisation (see Schemes 4,5). Moreover, inclusion of a catalytic amount of alcohol 18b in the reaction of 3 resulted in an even earlier onset of catalyst inhibition (Fig.…”
Section: Catalyst Deactivationmentioning
confidence: 70%
“…In conclusion, we have developed a synthetic route to a number of allocolchinoid analogues, including a formal synthesis of (±)-allocolchicine (±)-5 using a gold-catalysed direct arylation [1][2][3][4][5][6] in the key bond-forming step. The reaction is vulnerable to severe catalyst deactivation, with the likely cause identified as in situ inhibitor generation, involving a direct (uncatalysed) reaction of the substrate with the iodine(III) oxidant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations